Rationale and study design for an individualised perioperative open-lung ventilatory strategy with a high versus conventional inspiratory oxygen fraction (iPROVE-O2) and its effects on surgical site infection: study protocol for a randomised controlled trial. Issue 7 (31st July 2017) - Ferrando, Carlos; Soro, Marina; Unzueta, Carmen; Canet, Jaume; Tusman, Gerardo; Suarez-Sipmann, Fernando; Librero, Julian; Peiró, Salvador; Pozo, Natividad; Delgado, Carlos; Ibáñez, Maite; Aldecoa, César; et al.
Abstract : Introduction: Surgical site infection (SSI) is a serious postoperative complication that increases morbidity and healthcare costs. SSIs tend to increase as the partial pressure of tissue oxygen decreases: previous trials have focused on trying to reduce them by comparing high versus conventional inspiratory oxygen fractions (FIO2 ) in the perioperative period but did not use a protocolised ventilatory strategy. The open-lung ventilatory approach restores functional lung volume and improves gas exchange, and therefore it may increase the partial pressure of tissue oxygen for a given FIO2 . The trial presented here aims to compare the efficacy of high versus conventional FIO2 in reducing the overall incidence of SSIs in patients by implementing a protocolised and individualised global approach to perioperative open-lung ventilation. Methods and analysis: This is a comparative, prospective, multicentre, randomised and controlled two-arm trial that will include 756 patients scheduled for abdominal surgery. The patients will be randomised into two groups: (1) a high FIO2 group (80% oxygen; FIO2 of 0.80) and (2) a conventional FIO2 group (30% oxygen; FIO2 of 0.30). Each group will be assessed intra- and postoperatively. The primary outcome is the appearance of postoperative SSI complications. Secondary outcomes are the appearance of systemic and pulmonary complications. Ethics and dissemination: The iPROVE-O2 trial has been approved by the Ethics Review Board at the reference centre (the Hospital Clínico Universitario in Valencia). Informed consent will be obtained from all patients before their participation. If the approach using high FIO2 during individualised open-lung ventilation decreases SSIs, use of this method will become standard practice for patients scheduled for future abdominal surgery. Publication of the results is anticipated in early 2019. Trial registration number: NCT02776046; Pre-results.